(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents the lexicographic studies, their formation based on the creation of a specific writer, the aim and the role of the lexicographical works in defining the individual style of an author, the lexical content of the novel “Theorem” by Temurbek Turaboev for presenting the artistic thought in its entirety.